Factors affecting exclusive breastfeeding in term infants - Novitria Dwinanda (Paediatrica Indonesiana, 2018)
Background Exclusive breastfeeding by healthy mothers to their healthy, term babies who underwent vaginal birth, should be readily accomplished. However, exclusive breastfeeding by Indonesian mothers has declined.